PANDAA intentionally violates conventional qPCR design to enable durable, mismatch-agnostic detection of highly polymorphic pathogens - Iain J. MacLeod (Nature Portfolio, 2021)
Iain MacLeod et al. develop the Pan-Degenerate Amplification and Adaptation (PANDAA) point mutation assay to detect HIV drug resistance mutations. This method can be applied to any pathogen where target-proximal genetic variability hinders diagnostic development.